Serum Pharmacochemistry Analysis Combined with Network Pharmacology Approach to Investigate the Antiosteoporosis Effect of Xianlinggubao Capsule in vivo - Yun-Hui Xu; Yi-Chun Sun; Jie Liu; Hui-Xin Li; Chun-Yue Huang; Yuan-Yuan Pang; Tong Wu; Xiao Hu (Georg Thieme Verlag KG, 2020)
Xianlinggubao capsule (XLGB) is a traditional Chinese medicine multi-component herbal prescription and has been widely used in osteoporosis (OP) treatment. However, the underlying anti-OP mechanisms of XLGB have not been fully studied. In this study, an ovariectomized rat model of OP was established. The OP rats were orally administrated with XLGB, and then the main absorbed components in serum sample were assessed based on liquid chromatography-tandem mass spectrometry (LC-MS/MS). Subsequently, the potential anti-OP markers in XLGB were screened based on a network pharmacology strategy. Molecular docking analysis was used for confirmation. LC-MS showed 22 absorbed components in the serum sample of OP rat with XLGB treatment. Network pharmacology and pathway analysis suggested 19 potential anti-OP markers in XLGB. According to molecular docking process, most of the potential markers displayed strong interactions with the 22 absorbed components mentioned above. Besides, an absorbed component-potential marker-pathway network was further established. In conclusion, our data suggested the possible mechanisms for XLGB in OP treatment, in which the "multicomponents, multitargets, and multipathways" participated. Our article provided possible direction for drug discovery in OP and could help for exploring novel application of XLGB in clinical setting.